Tunjangan Fungsional dan Motivasi Kerja Pustakawan Universitas Hasanuddin - Tangngareng, Tasmin; Nasrullah; Mansur, Mujahidah; Tawakkal (Literatify : Trends in Library Developments, 2024)
This study investigates whether an increase in functional allowances can enhance the work motivation of librarians at the University of Hasanuddin Makassar Library. The primary research question is whether the increase in functional allowances leads to improved motivation among librarians. The objective of the study is to determine if raising functional allowances can boost librarians’ work motivation at this library. Employing a descriptive research design with a qualitative approach, data collection techniques included observation, document analysis, and interviews with five librarians from the University of Hasanuddin Makassar Library. The findings indicate that increasing functional allowances positively affects librarians’ work motivation, leading to greater enthusiasm and discipline in their work.